2013
DOI: 10.4236/oju.2013.37053
|View full text |Cite
|
Sign up to set email alerts
|

Nonpalpable Testicular Masses—Should We Be Worried?

Abstract: Objective: To report our experience of a contemporary series of patients who underwent radical orchidectomy for non-palpable testicular masses, in order to comment on their malignant potential and identify any factors predictive of a malignant outcome. Materials and Methods: We reviewed the case-notes of patients who underwent radical inguinal orchidectomy over a 22-month period between January 2010 and October 2011. Results: A total of 71 patients were analysed, with a mean (range) age of 45 years (17 -82). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…At primary diagnosis, malignant testicular tumors have a median size of 3 cm (IQR 1.8–4.5 cm) [ 27 ]. Abboudi et al also showed in 2013 that over two-thirds of testicular tumors < 1 cm were benign [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…At primary diagnosis, malignant testicular tumors have a median size of 3 cm (IQR 1.8–4.5 cm) [ 27 ]. Abboudi et al also showed in 2013 that over two-thirds of testicular tumors < 1 cm were benign [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a normal contralateral testis, inguinal RO is the standard of care for all males diagnosed with a testicular mass suspicious for malignancy or an indeterminate testicular mass, despite a significant risk of over treatment [7,8]. However, this must be balanced with the risks of under treatment (e.g., surveillance with the potential effects of delayed treatment on survival and the psychological burden of disease surveillance).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…However, RO can negatively impact fertility, endocrine function, sexual satisfaction as well as leading to anxiety and depression [5]. This is important as ~30% of ROs for impalpable testicular masses in post‐pubertal males and between 63%–94% in pre‐pubertal males are histopathologically benign [6–8]. The increasing application and widespread use of SUS and the limitations of SUS and scrotal MRI in their ability to accurately identify a testicular mass as either benign or malignant, represents a significant management dilemma for clinicians, particularly in the context of an indeterminate testicular mass [9].…”
Section: Introductionmentioning
confidence: 99%